Syntheses and characterization of two new layered ternary chalcogenides NaScQ2 (Q = Se and Te). (8th November 2022) - Panigrahi, Gopabandhu; Yadav, Sweta; Jana, Subhendu; Ghosh, Arghya; Niranjan, Manish K.; Prakash, Jai
Abstract : Two new metal ternary chalcogenides, NaScSe2 and NaScTe2, have been synthesized via high-temperature reaction. Abstract : Two new mixed metal ternary chalcogenides, NaScSe2 and NaScTe2, have been synthesized by the high-temperature reaction of elements using the sealed tube method. Single crystal X-ray diffraction studies show that both compounds are isostructural and adopt the trigonal crystal system with space group R 3̄ m with three formula units ( Z = 3). The NaScQ2 structure consists of three unique crystallographic sites: Na, Sc, and Q sites. The Sc atom in this structure sits at the center of an octahedron of six Q atoms. The six Sc–Q bonds are identical, but the geometry of ScQ6 is slightly distorted compared with the ideal octahedron. The ScQ6 octahedra are conjoined to adjacent units via edge-sharing to form two-dimensional layers of 2∞[ScQ2 ] 1− . Two such layers are separated by the filling of Na + cations, each surrounded by six Q atoms forming distorted octahedral geometry. These two chalcogenides are valence precise [Na 1+ Sc 3+ (Q 2− )2 ]. The optical absorption and thermal conductivity measurements were carried out on the polycrystalline samples of NaScQ2 . The optical bandgap value for NaScSe2 (1.5(1) eV) and NaScTe2 (1.2(1) eV) confirms their semiconducting nature. The high-temperature resistivity and Seebeck coefficient studies were also performed on a sintered polycrystalline sample of NaScTe2 . The emission spectroscopic analysis of the polycrystalline NaScSe2 was also analyzed to understand the fluorescence properties. DFT calculations were performed to study the electronic structure, optical, and thermoelectric properties of NaScQ2 . The COHP analysis shows stronger chemical bonding between the Sc and Te atoms compared with that of Na atoms in the NaScQ2 structure.